MAKNA KULTURAL DARI VARIASI UNGKAPAN TERIMA KASIH DALAM BAHASA JEPANG: DITINJAU MELALUI KARYA FILM HAYAO MIYAZAKI - Mukti, Rr. Savira Ayu; Didik Nurhadi; Urip Zaenal Fanani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Japan is a cultural country that also prioritizes the culture of gratitude. The existing culture of gratitude is manifested as an expression. The purpose of this study is to determine the various expressions of gratitude in Japan. Each expression of gratitude also has cultural significance or cultural significance. This research is a qualitative descriptive study using data collection techniques such as listening, notetaking, and literature study. The sources of expressions of gratitude that appear in the film Kimitachi wa Dou Ikiru ka. The results of this study indicate the existence of several unique expressions of gratitude that are almost never found in other countries.